2009
DOI: 10.4110/in.2009.9.5.179
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic and Therapeutic Potential of Asp f1 Epitopes in Naïve and Sensitized BALB/c Mice

Abstract: BackgroundThe present study examines a hypothesis that short allergen-derived peptides may shift an Aspergillus fumigatus (Afu-) specific TH2 response towards a protective TH1. Five overlapping peptides (P1-P5) derived from Asp f1, a major allergen/antigen of Afu, were evaluated for prophylactic or therapeutic efficacy in BALB/c mice.MethodsTo evaluate the prophylactic efficacy, peptides were intranasally administered to naïve mice and challenged with Afu-allergens/antigens. For evaluation of therapeutic effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…Thus, they establish the use of allergen peptides to control allergenic reactions in mice and open the way for human study. 27 Our analysis also predicted the same B cell and T cell (MHC-II class) epitopic peptides that are used by Chaudhary et al and suggested a strong correlation between in silico prediction and experimental evidences. We further analyze the epitopic data to screen common epitopic peptides for mouse and human so that they can be tested first on mouse model of A. fumigatus -induced allergy or infection model, and then the promising results from these studies can go for clinical trials for human use.…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…Thus, they establish the use of allergen peptides to control allergenic reactions in mice and open the way for human study. 27 Our analysis also predicted the same B cell and T cell (MHC-II class) epitopic peptides that are used by Chaudhary et al and suggested a strong correlation between in silico prediction and experimental evidences. We further analyze the epitopic data to screen common epitopic peptides for mouse and human so that they can be tested first on mouse model of A. fumigatus -induced allergy or infection model, and then the promising results from these studies can go for clinical trials for human use.…”
Section: Resultssupporting
confidence: 67%
“…A. fumigatus not only causes ABPA but also is responsible for allergic Aspergillus sinusitis, hypersensitivity pneumonitis, and IgE-mediated asthma. 27 Various strategies have been used to treat allergies such as allergen avoidance and elimination, subcutaneous injection of allergenic extract, and allergen shots. 28 Immunotherapy involves the subcutaneous administration of gradually increasing quantities of allergens or allergen epitopic peptides until a dose has been reached that is effective enough to induce immunologic tolerance to these allergens.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Asp F1 is a ribotoxin and considered the main allergen of A. fumigatus . It was shown that the Asp F1 P1 peptide was able to regulate the allergic response in animals challenged with A. fumigatus allergens and antigens ( Chaudhary et al., 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, these five proteins with high affinity binding to MHC class I or II epitopes could be used to characterize constituent peptides and develop vaccine candidates for invasive Aspergillus infections or therapeutics for allergy immunotherapy for chronic allergic bronchopulmonary aspergillosis. The promise of this approach is supported by prior work demonstrating that peptides from the protein Asp f1 stimulate the production of Th1 cytokines [60]. However, these proteins have not yet been validated as effective vaccine components.…”
Section: Aspergillosismentioning
confidence: 99%